Exercise facilitates post-stroke recovery through mitigation of neuronal hyperexcitability via interleukin-10 signaling - Schmidt-Pogoda, A.; Ruck, T.; Strecker, JK; Hoppen, M.; Fazio, L.; Vinnenberg, L.; Maus, B.; Wachsmuth, L.; Cerina, M.; Diederich, K.; Lichtenberg, S.; Abberger, H.; et al. (Nature communications, 2025)
Physical exercise is an effective therapy for improving stroke recovery. However, the exact underlying molecular mechanisms of exercise-enhanced neuronal repair remain unclear. As exercise affects the immune system in healthy individuals, and the immune system in turn influences recovery after stroke, we hypothesized that immune mechanisms play a role in exercise-induced neurological recovery. Using a model of ischemic stroke in adult male mice, we here show that the presence of regulatory T cells (Treg) within the ischemic brain is a prerequisite for exercise-enhanced functional and structural recovery. Treg prevent excessive and sustained hyperexcitability of periinfarct neurons via IL-10 signaling. This reduced hyperexcitability precedes alterations in neuronal connectivity, which underlie functional improvement. Together, we delineate the interaction of exercise-therapy, the immune system and functional recovery after ischemic stroke. Our findings can have translational relevance for further development of immune-targeted therapies. Exercise promotes recovery after stroke, but the underlying mechanisms are unclear. Here, the authors show that regulatory T cells enable exercise-induced repair by reducing neuronal hyperexcitability via interleukin-10, linking immunity to functional regeneration.